DETERMINATION OF HEAVY MACHINES PERFORMANCES BY USING A MEASURING SYSTEM WITH TELEMETRIC SYNCHRONIZATION AND TRANSMISSION OF SIGNALS - Radoicic, Goran Nikola; Jovanović, Miomir Ljubomir (Journal of Applied Engineering Science, 2018)
This paper presents the investigation of importance for determining the dynamic structural response of heavy lifting machines subjected to extreme external effects. A measuring system for the experimental investigation of the dynamics of heavy lifting machines is proposed. It shows the experimental testing results of carrying structures for several classes of hoisting and an export mining machine. The results refer to the most important dynamic parameters. The dynamic parameters also include the duration of transient phenomena in handling lifting structures and structural damping. A technical solution based on the measuring chain that is integrated into the mining export plant information system was developed in the research. The recommendation to choose optimal measuring equipment for this kind of measurement is given to manufacturers and users on the basis of the experience gained in the design and implementation of specific measuring systems. The technical specification of amplifiers and transducers that should be developed for this kind of measurement is also proposed.